Productive Waqf Fund Management Strategy - Muhammad Ulul Azmi; Setiawan Bin Lahuri; Fazari Zulhasmi Kanggas; Imam Kamaluddin; Soritua Ahmad Ramdani Harahap (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
This article aims to provide an example for waqf management institutions in developing the benefits of productive waqf by implementing a good waqf management strategy and following the concept and purpose of waqf. With the increasing public interest in waqf and the increasing number of waqf management institutions throughout the world and especially in Indonesia. Along with that, there has not been a desire that can be emulated by waqf management institutions in determining the management strategy of productive waqf funds to develop the benefits of productive waqf itself. This type of research is qualitative research with data collection techniques conducted by conducting interviews with nadzir waqf in PM. Darussalam Gontor. This research shows that PM. Darussalam Gontor has a unique strategy in managing productive waqf funds while still looking at the purpose of the existing waqf, more than that, many communities around the boarding school can also benefit from productive waqf in PM. Darussalam Gontor. This research is expected to be a guide in developing the benefits of productive waqf in waqf management institutions in Indonesia.